Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa - Channing, A.; Measey, G.j.; Villiers, A.l. De; Turner, A.a.; Tolley, K.a. (Zootaxa, 2017)
A molecular and morphological study of the Mountain Toadlets, previously included in Capensibufo rosei, showed that there are several previously unrecognised species in this group. We describe three new species from the Hawekwas, Hottentots-Holland, Groenland and Riviersonderend Mountains; the DuToitskloof Mountains, and the Akkedis, Koeël and Kleinriviers Mountains, South Africa. Capensibufo rosei is restricted to the Table Mountain chain of the Cape Peninsula.